Products with organic certification: Do Brazilian consumers perceive their attributes? - de Lima, Anderson Rodolfo; Scalco, Andrea Rossi [UNESP]; Ganga, Gilberto Miller Devós (FapUNIFESP (SciELO), 2022)
Paper Aims: This work aims to identify the socio-environmental attributes related to the label ‘Brazilian Organic Product – BOP-perceived by consumers of organic foods. Originality: This paper is pioneering in the understanding of the attributes of BOP label in Brazil by consumers. Also, is unique in exploring the dimensions “organic’, “environmental” and “social” based on Brazilian law regarding organic food and the Guidelines of the Certifiers of Organic Products in Brazil. Research method: A survey was conducted with 106 consumers of organic foods and an exploratory factor analysis (EFA) was carried out. Main findings: Results showed that eight dimensions of attributes (Labor Laws and Social Incentive; Social and Environmental Practices; Environmental Management; Social and Environmental Protection; Environmental Preservation; Natural Products; Animal and Social Welfare; Non-renewable resources) influence consumer’s perception about the BOP label. Implications for theory and practice: For theory this study shows how consumers perceive socio environmental attributes through labels and how this perception can motivate the purchase. For practice, intended to provide insights for marketing managers to better improve information on the labels Also, provide information to public policy managers to improve policies that can reach out more consumers.
Keywords: Certification; Exploratory factor analysis.Organic; Socio-environmental